Analisis Pendekatan Struktural dan Religius Cerpen “Titah yang Berkuasa” Karya Dede Soepriatna - Khairunnisa, Riska; Abdurahman, Abdurahman (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
This research aims to analyze religious and structural values in Dede Soepriatna's short story "Titah yang Berkuasa" through an integrated religious and structural approach. Employing a qualitative descriptive method with content and structural analysis techniques, this study reveals various spiritual values implicit within the narrative of this contemporary Indonesian literary work. The analysis results demonstrate fundamental religious values such as destiny (qada and qadar), tawakkal (submission to God's will), sacrifice, betrayal, and divine justice. The character Roro Oyi represents spiritual steadfastness and surrender to the Creator amidst life's trials, while King Amangkurat's character critiques the abuse of power that contradicts moral-religious principles. Structurally, the short story presents a complex plot with effectively developed central conflict, multidimensional characterization, and rich symbolism that deepens the spiritual meaning of the narrative. The research findings confirm that literature can function as an effective medium for moral and religious education without sacrificing narrative integrity. The integration of religious and structural approaches provides a holistic perspective in understanding how spiritual messages are conveyed through formal beauty, offering a literary appreciation model that harmoniously combines ethical and aesthetic dimensions.